Innovative ridge furrow technology impact on area, productivity and economics of pearl millet: A case study - Singh, Y P; Tomar, Sandeep S; Yadav, Ravi; Gurjar, Ravi; Singh, Sudhir (Indian Farming, 2022)
Pearl millet is also nutritionally superior and rich in micronutrients and can mitigate malnutrition and hidden hunger. The ridge furrow making in standing crop of pearl millet at 40 cm spacing by ridge furrow maker at 25 DAS gave significantly higher yield, net income, and WP. Impact of weed and rainwater conservation with ridge furrow at 40 cm spacing in standing pearl millet crop was adopted in 1.953 lakh ha area and additionally gave `255.8 crores, while saving `18 crores of pearl millet growers of the Chambal division. This technology sustainably enhanced productivity for nutritional security and , economic profitability, saving cultivation.